The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1007/bf02245296
|View full text |Cite
|
Sign up to set email alerts
|

Role of spinal serotonin1 receptor subtypes in thermally and mechanically elicited nociceptive reflexes

Abstract: The ability of 5-HT1A and 5-HT1B agonists to alter a spinal animal's nociceptive threshold was examined using two analgesiometric tests. In the spinal withdrawal reflex test, administration of the selective 5-HT1A agonists ipsapirone, gepirone and PAPP resulted in significant dose-dependent increases in receptive field (RF) area for withdrawal reflexes when compared to predrug baseline values, indicating an increase in nociceptive sensitivity. The average overall percent maximal increase in RF area following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Pretreatment with naloxone prevented the increase of 5-HT in both areas (Fig. 5); [F (1,20) ¼10.7; p < 0.01], [F (1,20) ¼12.2; p < 0.01] for pons and cortex respectively.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Pretreatment with naloxone prevented the increase of 5-HT in both areas (Fig. 5); [F (1,20) ¼10.7; p < 0.01], [F (1,20) ¼12.2; p < 0.01] for pons and cortex respectively.…”
Section: Resultsmentioning
confidence: 95%
“…The levels of serotonin in the cortex and in the pons were significantly increased by the antinociceptive combination of PARA 100 mg/kg and morphine 3 mg/kg, while they did not change the values of controls when given alone (Fig. 4); the interaction test showed a potentiation in the two areas [F (1,20) ¼15.2; p < 0.01], [F (1,20) ¼28.2; p < 0.01] for pons and cortex respectively. Pretreatment with naloxone prevented the increase of 5-HT in both areas (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have shown that the nociceptive test and the quality of the noxious stimulus used for assessing animal sensitivity are of critical importance Murphy et al 1992). A great majority of behavioural tests used in studies with 5-HT or 5-HT receptor agonists are thermal tests and mainly the tail-flick test.…”
Section: Introductionmentioning
confidence: 99%
“…Under different experimental conditions serotonin may facilitate, produce no effect on, or reduce, behaviourally defined analgesia [9]. The serotoninergic pathway in the CNS can mediate antinociception and is involved in the expression of the antinociceptive action of opioids [10].…”
Section: Introductionmentioning
confidence: 99%